Community happiness the distinct role of environment setting relatedness / Siti Rasidah Md Sakip, Khalilah Hassan and Azran Mansor - Siti Rasidah, Md Sakip; Khalilah, Hassan; Azran, Mansor (Universiti Teknologi MARA, Perak, 2016)
This study argues that although scenic beauty, preference, and restoration are correlated due to their functional significance over evolution. A total of 86 respondents were randomly selected involving in this study. Exploratory Factor Analysis (EFA) is used in the early stages to gather information about the interrelationships among variables. The Cronbach’s Alpha (α) value was used to determine the level of reliability through the internal consistency for each factor.The objective of this paper is to determine the factors that influence on Happiest Selama Community. The output will be used to find the relationship between environmental setting and factors of quality of life among residents in Selama district.